Cytochrome P4503A activity affects the gender difference in the development of steroid‐induced osteonecrosis in rabbits. Issue 2 (29th October 2013) - Ikemura, Satoshi; Yamamoto, Takuaki; Motomura, Goro; Yamaguchi, Ryosuke; Zhao, Garida; Iwasaki, Kenyu; Iwamoto, Yukihide
Summary The aim of this study was to investigate cytochrome P4503A activity and its correlation with the development of osternecrosis (ON) among male and female steroid‐treated rabbits. Forty adult rabbits (male, n = 20; female, n = 20) were injected once with 20 mg/kg of methylprednisolone intramuscularly. Haematologically, cytochrome P4503A activity was measured by plasma 1′‐hydroxymidazolam‐to‐midazolam (1′‐OH‐MDZ/MDZ) ratio just before and 48 h after the steroid injection. We also measured the levels of oestradiol every week. Both femora and humeri were histopathologically examined for the presence of ON. Fifteen of 20 male rabbits (75%) developed ON, while 6 of 20 female rabbits (30%) did so. There was a significant difference in the rate of incidence of ON between male and female rabbits (P = 0.010). The 1′‐OH‐MDZ/MDZ ratio in female rabbits just before, as well as 48 h after the steroid injection was significantly higher than that in male rabbits (P = 0.039 and P = 0.001 respectively). In addition, 1′‐OH‐MDZ/MDZ ratio in female rabbits significantly increased in 48 h after the steroid injection (P = 0.044), while that in male rabbits did not so (P = 0.978). The levels of oestradiol in female rabbits were significantly higher than those in male rabbits during the experimental period (P = 0.008). In conclusion, this study indicates that the gender difference in cytochrome P4503A activity may be one of the important factors for the development of steroid‐induced ON, possibly due to the effects of oestradiol.